2022
DOI: 10.3171/2020.10.jns203366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supramarginal resection on survival outcomes after gross-total resection of IDH–wild-type glioblastoma

Abstract: OBJECTIVE The authors’ goal was to use a multicenter, observational cohort study to determine whether supramarginal resection (SMR) of FLAIR-hyperintense tumor beyond the contrast-enhanced (CE) area influences the overall survival (OS) of patients with isocitrate dehydrogenase–wild-type (IDH-wt) glioblastoma after gross-total resection (GTR). METHODS The medical records of 888 patients aged ≥ 18 years who underwent resection of GBM between January 2011 and December 2017 were reviewed. Volumetric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…This has led to several studies proposing that SMR of the T2/FLAIR region beyond the contrastenhancing portion might provide an additional benefit on a patient's OS. [16][17][18][19][20][21][22] However, there has been variability in these results, likely due to tumor subtypes and individual characteristics. 33 In this current study, we implemented tumor invasiveness profiling to assess the influence of SMR on OS in patients with the most aggressive GBM subtype (IDH-wild type).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to several studies proposing that SMR of the T2/FLAIR region beyond the contrastenhancing portion might provide an additional benefit on a patient's OS. [16][17][18][19][20][21][22] However, there has been variability in these results, likely due to tumor subtypes and individual characteristics. 33 In this current study, we implemented tumor invasiveness profiling to assess the influence of SMR on OS in patients with the most aggressive GBM subtype (IDH-wild type).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Supramarginal resection (SMR)-defined as resection beyond the T1 contrast enhancement within the boundaries of the FLAIR hyperintense signal-has been shown to improve overall OS in GBM. [16][17][18][19][20][21][22] However the benefit of SMR may not be uniform across all GBM patients, and intrinsic tumor characteristics such as tumor cell distribution and genetic profiles might impact the survival benefit conferred by SMR. 19 New advanced mathematical models based on patientspecific radiographic characteristics have provided new insights into GBM behavior and might help elucidate SMR benefit on OS.…”
mentioning
confidence: 99%
“…In a recent work published in 2020 by Molinaro and colleagues was showed that resection of NE peritumoral region increased median OS to 31 months in patients younger than 65 years of age (Molinaro et al, 2020). On the contrary, patients older than 65 years of age did not have any benefit from resection of NE perilesional region (Molinaro et al, 2020), despite some authors found contrary results (Vivas‐Buitrago et al, 2022). This huge increase of the median OS (almost 2 years on median OS), in contrast with the commonly reported median OS of 14–20 months, is counterbalanced by the increase risk of post‐operative neurological deficit in case of resection of the NE peritumoral region, although use of neurophysiological monitoring and pre‐operative diffusion tensor imaging should reduce this risk (Bello et al, 2008; Carrabba et al, 2016; De Witt Hamer et al, 2012; Di Cristofori et al, 2021; Raabe et al, 2014).…”
Section: Translational Aspectsmentioning
confidence: 99%
“…Nowadays it is clearly known that the OS of patients with GBM is significantly affected by the extent of CE tumor resection at brain MRI (Al‐Holou et al, 2020; Hervey‐Jumper & Berger, 2016; Li et al, 2016; Sanai et al, 2011). Less clear is how surgical resection of T2W FLAIR peritumoral hyperintense zone can affect prognosis of patients with GBM; although several authors support the idea that supramarginal resection can increase OS in patients with GBM (Molinaro et al, 2020; Pessina et al, 2017; Vivas‐Buitrago et al, 2022), while others do not (Jackson et al, 2020). The presumed benefit of resection of NE perilesional zone of GBM is questioned by the fact that supramarginal resection may be related to an increased risk of post‐operative neurological deficits (Molinaro et al, 2020) which may in turn adversely affect the OS of patients (approximately 6 months on median OS), abrogating all the benefits of resection (McGirt et al, 2009; Rahman et al, 2017).…”
Section: Translational Aspectsmentioning
confidence: 99%
“…Each therapeutic modality has severe conceptual limitations. The surgical gold standard for the treatment of tumors in general is a complete tumor resection, which is however not feasible for principal reasons in the case of the infiltrative GBM; the present resection policy is restricted to a gross total tumor removal reflecting a definition of the extension of the neoplasm based on neuroimaging criteria; some aim at so-called supramarginal resections, but microscopic distant satellites after resection may still be left behind after surgery [3,4].…”
Section: Introductionmentioning
confidence: 99%